Speciation of organometallic of tin, lead and mercury in environmental samples - Nsengimana, Hermogene (My University, 2008)
Abstract Organic derivatives of tin, lead, mercury are the most widely distributed organometallic ecotoxicants in the environment. While some of these organometallic compounds exist in the environment as a result of direct discharge, anthropogenic emissions alone cannot explain the ubiquity, for example, of the organomercury and organolead compounds in marine and fresh waters, sediments and biota. It is known that some organometallic compounds are formed via a bioconversion from the inorganic contaminants. Depending on the source, they can enter the environment in varied forms inorganic species of different stability. These can be bio-converted further by environmental biota; for instance metals such as tin and lead can be discharged into the environment in the form of organometallic species which can undergo further transformation. Determination of organometallics in environmental and biological samples is difficult due to matrix effect and their low concentrations. Separation and preconcentration is necessary to enhance final determination. Speciation studies are even more complicated. Speciation is an important aspect and gives information about bioavailability of the metal thus their toxicity. This work focused on the development of a method for speciation of organospecies of tin, lead and mercury. A new derivatisation agent has been synthesised and used successfully. SLM probe extraction has been exposed to a new matrix. Different environmental samples have been analysed for organo-species of tin and lead and their pathways predicted. The SLM probe extraction gives the advantage of carrying out several extractions, reduction of the amount of solvent used and avoidance of emulsion problems. A simple system has been developed and applied successfully on organotin and organolead extraction from aqueous environmental sample. For reproducibility of the results, pH, salinity, stirring rate and extraction time were optimized. An analytical method for simultaneous in situ ethylation, using new derivatisation agent bromomagnesium tetraethylborate (Et4BMgBr), of organotin and organomercury compounds in sediment samples was developed. The determination of mercury and tin compounds is achieved by species-specific isotope dilution, derivatisation and gas chromatography – inductively coupled plasma mass spectrometry (GC-ICP-MS). In derivatisation, pH and the amount of derivatisation agent were studied. Percentage recovery and accuracy of the method was confirmed by comparison of experimental results with sediment and plant certified reference material (IAEA 405 for sediment and CRM 279 for plant). Although organolead compounds as a gasoline additive are banned in most countries, in some regions, lead is still added to gasoline in varying proportions of different tetraalkyllead compounds and contamination by organolead compounds is still present at different places, e.g.: lead alkyl manufactures The use of both tetraalkyllead and butyltin is banned (tetraalkyllead as gasoline additive and butyltin in antifouling pints and PVC materials). This work focussed on their conversion in water and soil. This should provide an insight into their presence in the environment and an understanding of their degradation in the environment. A method for full speciation and determination of alkyl lead and inorganic lead (II) after the tetramethyllead degradation in aqueous samples has been developed. This was accomplished by in situ derivatisation with sodium tetraphenyllead borate NaB(Ph)4 derivative. The derivatisation was carried out directly in the aqueous sample and the derivatives were extracted using the supported liquid membrane probe extraction (SLMPE). The extracted analytes were then transferred to a GC/MS for separation and detection. This study focused on the transformation of tetramethyllead in aqueous media, at different concentration of major elements, K+,Na+,Ca++, Mg++,Cl-,SO4 --. Adsorption / desorption on soil of ionic organolead and organotin were also studied. As South Africa is one of the world’s major producers of coal, mercury should be monitored as it is a side product in coal combustion. The trend of inorganic mercury and methylmercury in sediment found in this work indicated a possible methylation of inorganic mercury to methylmercury in Klipriver sediments.
Keywords: organometallic compounds; lead; tin; mercury; environmental pollution; speciation